SISTEM KEAMANAN KONFIGURASI WEB MENGGUNAKAN REST API BERBASIS JWT HMAC SHA-512 - Rafi Fredy Septianto, (2021)
The current development of WS is a trend, namely the transfer of state representation (break) and simple object access protocol (SOAP). The results of studies that have been created in mobile computing applications show that the size of messages in a quiet Web Service reaches nine to ten times smaller than the size of SOAP-based WS messages. However, the REST is very low in terms of security. Securing RESTfulWS includes securing data and all communications to protect data confidentiality and integration. To work around this issue, the JSON Web Token (J WT) is used. This step was done in a previous study, which used JWT with the commonly used HMACSHA-256 algorithm, so that it could be a separate threat to security. The results of the study stated that the comparison of the implementation of SHA-256 and SHA-512 algorithms on 64-bit Intel architectures resulted in sha-512 performance 50% better than SHA-256.